STUDI ANALISIS METODE ISTINBATH HUKUM IMAM SYAFI’I DAN IMAM HANAFI TENTANG BA’I AL MU’ATHOH - Dudang Gojali; Hapid Ali (UIN Sunan Gunung Djati Bandung, 2021)
The aim of this study is to know the different result of law istinbathwhich is used by Imam Syafi’i and Imam Hanafi in legalizing the law of al-mu’athoh trade. This study used qualitative design in library research method, in collecting data, this study focused on primary and secondary sourses. The result of this study showed that there is different law istinbath used by Imam Syafi’i which focused on bayani method in different formulations and Ijma’ and qiyas enforcement as a hujjah (law sourse) in formulating syara’ law. Thus it showed that the law of al-mu’athoh trade is invalid because the sincerity and agreement of transaction could not be found except by utterance of ijab and qabul between them in other that it far from abuse practice, while Imam Hanafi more focused on bayani method in diffrent approach and focused on qiyas development by istihsan and urf approach gained the result of al-mu’athoh trade is allowance and valid in diversities transaction except in marriage because in ijab and qabul, it did not required to uttarence by words, it is enough to have sincerity and agreement between both of them